Gaya Hidup Fomo Pada Remaja Akhir Di Era Digital: Library Research - Sentit Rustiani; Fitri Aulia Rahman; Miftakhul Rohmah (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2023)
As a result of globalization, various social changes have occurred in Indonesian society, especially teenagers who are open to change. Various things are changing, such as the lifestyle of today's teenagers who are more consumptive, especially because of the various social media that exist today and the emerging marketplaces that offer various conveniences in shopping, making late teenagers become figures who are easily consumed by various existing advertisements, making them to have a fomo lifestyle that buys an item without considering its use but based on desire. The method used is a qualitative method using interview instruments. Data analysis in this study shows that teenagers who easily accept change with high egos cause teenagers to have a fomo (fear of missing out) lifestyle due to the various social media that exist, making it easier for them to find out about various viral items. As a result, there is a shift in lifestyle from teenagers of the past compared to today's teenagers who are more consumerist.